2017
DOI: 10.1080/01635581.2017.1283422
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Comprehensive Nutritional Index and the EORTC QLQ-H&N35 in Nasopharyngeal Carcinoma Patients Treated with Intensity-Modulated Radiation Therapy

Abstract: This study aimed to explore the relationship between the comprehensive nutritional index (CNI) and quality of life in nasopharyngeal carcinoma (NPC) patients receiving intensity-modulated radiation therapy (IMRT). The nutritional index, which includes total lymphocyte count, hemoglobin and albumin levels, body mass index, and usual body weight percentage, was evaluated pre-treatment and post-treatment in patients who underwent IMRT. The quality of life of NPC patients was measured by the European Organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…For all the domains, an increase in scores in the middle of treatment, and maintenance of this higher score until the end of treatment, was observed. Other studies also observed an increase in scores for symptoms with greatest impact on nutrition after treatment [ 14 , 22 ], leading to a reduction in food intake and favoring the occurrence and/or worsening of nutritional status [ 31 , 32 ]. On the other hand, previous studies found a positive association between nutritional status and QoL [ 16 , 22 ], as expected.…”
Section: Discussionmentioning
confidence: 98%
“…For all the domains, an increase in scores in the middle of treatment, and maintenance of this higher score until the end of treatment, was observed. Other studies also observed an increase in scores for symptoms with greatest impact on nutrition after treatment [ 14 , 22 ], leading to a reduction in food intake and favoring the occurrence and/or worsening of nutritional status [ 31 , 32 ]. On the other hand, previous studies found a positive association between nutritional status and QoL [ 16 , 22 ], as expected.…”
Section: Discussionmentioning
confidence: 98%
“…For the group in total, the mean values of HRQoL scores were in general most severe at this time point. For patients treated with RT, this is the time point when the systematic daily support from the healthcare system during treatment ends, i.e., at a time point when nutritional status [16,17] and HRQoL [22,23] often are at their worse. This indicates the importance of extra support to the patients when returning home after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have confirmed that, [15][16][17][18][19] in patients with NPC, enteral nutrition treatment shown to decrease the CCRT toxicity, the weight loss, and the radiotherapy interruption rate. [21][22][23][24][25][26] Very little was found in the literature on the role of HEN in bone marrow suppression of patients with NPC. 20 WBC and PLT are also important indicators that affect the course of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the literature review, most studies focused on the improvement of weight, quality of life, and dryness of mouth in patients with HNC during radiotherapy. [21][22][23][24][25][26] Very little was found in the literature on the role of HEN in bone marrow suppression of patients with NPC.…”
Section: Discussionmentioning
confidence: 99%